Use of etanercept to treat toxic epidermal necrolysis in a human immunodeficiency virus-positive patient - Yung-Yi Lee; Jui-Hung Ko; Chia-Hung Wei; Wen-Hung Chung (Wolters Kluwer Medknow Publications, 2013)
Toxic epidermal necrolysis (TEN) is an uncommon and severe cutaneous adverse drug reaction that causes disseminated necrosis of epidermal cells and mucocutaneous detachment. Here, we report the case of a 32-year-old man with human immunodeficiency virus infection who presented with generalized violaceous macules and blister formation 4 days after the administration of mefenamic acid and amoxicillin for a dental procedure. Additional symptoms included oral ulcers and conjunctivitis. Results of skin biopsy were compatible with Stevens-Johnson syndrome (SJS). SJS progressed to TEN within 2 days. Etanercept treatment showed a dramatic improvement in the symptoms of mucocutaneous lesions. To our knowledge, this is the first report on the treatment of TEN using etanercept in a human immunodeficiency virus-positive patient.